STUDI KORELASIONAL ANTARA CITRA PERUSAHAAN dan LOYALITAS BUSINESS CUSTOMERS pada PT SAUNG ANGKLUNG UDJO di BANDUNG - Lelywati Idham Suryana; Maharani Negara (SCHEMA (Journal of Psychological Research), 2009)
This Study was proposed to test a conceptual framework of correlating corporate image with the business customers in segment of the tourism industry. The data were obtained with the correlational method to the 36 participants who are the Manager of those business customers of Saung Angklung Udjo, PT. On addition, the sample were solicited with purposive sampling method. To measure the corporate image as the 1st variable in this study, theory from Frank Jefkins (1999) were used. In other hand, the measurement of business customers’ loyalty as the 2nd variable and had been operationalized according to the customer loyalty studys from Morais et. at (2004). Using the Rank Spearman’s correlation coefficient, with significance level 0.05, rs = 0.662, tcal> and dk = 34, the results indicated that the corporate image was positively associated with the business customers’ loyalty. The findings revealed that if business customers perceived that corporate already had a negative image, they in turn showed the low loyalty to the corporate. Further, determination coefficient resulted d = 43,82. This finding supported that, in this case, corporate image as the variable gave the contribution as much as 43,82% to the business customers’ loyalty.